The Analysis of Geometrical Reasoning Ability Viewed from Self-Efficacy on Connected Mathematic Project (CMP) Learning Etnomathematics-Based - Damaryanti, Desi Dwi; Mariani, Scolastika; Mulyono, Mulyono (Department of Mathematics, Universitas Negeri Semarang, 2017)
The purpose of this research was to know the geometrical reasoning ability of the students viewed from the self-efficacy through the learning of Connected Mathematic Project (CMP) ethnomathematic-based. The type of this research was qualitative which was descriptive. To obtained the validity of the qualitative data, the checking technique used in this research was sources triangulation, which had been done by comparing the suitability of the obtained data from the results of the interview and the test. Population of this research was the students of grade VIII at SMP Negeri 1 Sidoharjo and the sample was the students from VIII A Class. At the final, 12 research subjects were chosen to represent the group of level 1 self-efficacy, level 2 self-efficacy, level 3 self-efficacy, level 4 self efficacy, level 5 self-efficacy, and level 6 self-efficacy. In this research, there was a finding which shows us that the students with high self-efficacy had low ability to finish the geometrical reasoning ability test, while the students with low self-efficacy had the ability to finish the geometrical reasoning ability test. The factors which affected the finding were the motivations and the interest of learning mathematics which was affecting the attitude of the students in the classroom.